Effect of SiMg alloy on inclusions and microstructures of 16Mn steel - Wen, B; Song, B; Pan, N; Hu, Q Y; Mao, J H (Ironmaking & steelmaking, 2011)
The effects of cooling methods and Mg content on the inclusions and microstructures of 16Mn steel were observed, and the mechanism of intragranular ferrite nucleation induced by Mg containing inclusions is discussed. The results show that trace amounts of Mg in steel can induce intragranular ferrite nucleation. With increasing Mg content, the percentage of intragranular ferrite increases, while the optimum Mg content is ∼0·0048 wt-%. The appropriate cooling methods are furnace cooling to 1473 plus water cooling and water cooling. The lattice disregistry among MgAl 2 O 4 , MgO and ferrite-Fe phase is very small, and there is a Si enriched zone on the inclusions, which both contribute to the nucleation of intragranular ferrite.